2023
DOI: 10.5455/medscience.2023.04.056
|View full text |Cite
|
Sign up to set email alerts
|

The effects of proton pump inhibitors on the development of post-stenting major adverse cardiovascular events in patients with acute coronary syndrome

Abstract: Proton pump inhibitors (PPIs) are recommended for the prevention of gastrointestinal bleeding in acute coronary syndrome (ACS) patients who receive dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) but have been associated with an increased risk of major adverse cardiovascular events (MACE) in these patients. We aimed to investigate the relationship between serum asymmetric dimethylarginine (ADMA) and copeptin levels and MACE in those who started on imminent DAPT and PPI therapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Due to the concerns about antiplatelet attenuation with PPIs and the increased risk of worse cardiovascular outcomes, many clinicians have explored the use of H2RAs for patients on dual antiplatelet therapy [59]. A study in 2014 by Luo et al found that H2-receptor activation exaggerated myocardial injury by promoting myocardial mitochondrial dysfunction and by increasing cardiac vascular endothelial permeability [60].…”
Section: Medical Therapymentioning
confidence: 99%
“…Due to the concerns about antiplatelet attenuation with PPIs and the increased risk of worse cardiovascular outcomes, many clinicians have explored the use of H2RAs for patients on dual antiplatelet therapy [59]. A study in 2014 by Luo et al found that H2-receptor activation exaggerated myocardial injury by promoting myocardial mitochondrial dysfunction and by increasing cardiac vascular endothelial permeability [60].…”
Section: Medical Therapymentioning
confidence: 99%